2010
DOI: 10.1182/blood-2009-03-211003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative DNA methylation predicts survival in adult acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is characterized by molecular heterogeneity that is not fully reflected in the current classification system. Recent insights point toward a significant role of aberrant DNA methylation in leukemogenesis. Therefore, we investigated the prognostic impact of DNA methylation in AML. To screen for promoter methylation in AML we applied a combination of base-specific cleavage biochemistry and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 37 publications
4
118
1
1
Order By: Relevance
“…It was first discovered in 2006 by Takahashi and Yamanaka through the overexpression of four key transcription factors, Oct4, Sox2, Klf4 and c-Myc, which resultes changes in the epigenome of the cells, therefore the cells requires and re-establishs the characteristic of pluripotent stem cell (Firas et al, 2015;Takahashi and Yamanaka, 2006). Recent studies (Claus et al, 2013;Bullinger et al, 2010;Kon Kin et al, 2015) were confirmed that the Oct4-Sox2-Nanog network was required for the activation of self-renewal regulators and showed that several genes have been identified as hypermethylated, such as tumor suppressor genes, cell-cell signaling and cell adhesion molecules. Thus, hypermethylation of genes might involve in myelopoiesis.…”
Section: Discussionmentioning
confidence: 96%
“…It was first discovered in 2006 by Takahashi and Yamanaka through the overexpression of four key transcription factors, Oct4, Sox2, Klf4 and c-Myc, which resultes changes in the epigenome of the cells, therefore the cells requires and re-establishs the characteristic of pluripotent stem cell (Firas et al, 2015;Takahashi and Yamanaka, 2006). Recent studies (Claus et al, 2013;Bullinger et al, 2010;Kon Kin et al, 2015) were confirmed that the Oct4-Sox2-Nanog network was required for the activation of self-renewal regulators and showed that several genes have been identified as hypermethylated, such as tumor suppressor genes, cell-cell signaling and cell adhesion molecules. Thus, hypermethylation of genes might involve in myelopoiesis.…”
Section: Discussionmentioning
confidence: 96%
“…27 Using a supervised approach, Bullinger et al 27 demonstrated a significant association of altered DNA methylation and patient outcome (good or poor survival) of AML patients. Moreover, the authors were able to build a predictive model based on quantitative DNA methylation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors were able to build a predictive model based on quantitative DNA methylation patterns. 27 However, recent studies reported that there is little relation between the degree of demethylation following hypomethylating treatment and hematologic response in patients with MDS. 28 In other words, methylation is not a predictive marker of response to hypomethylating agents for MDS patients, and therefore we cannot decide which patient can be a good candidate to receive these drugs taking only in account the degree of methylation.…”
Section: Discussionmentioning
confidence: 99%
“…13 To obtain a first estimation of whether and to what extent ICSBP transcription is downregulated and whether there is an association between downregulation of ICSBP and recurrent cytogenetic aberrations of myelodysplastic syndrome (MDS) and AML, we screened the PubMed GEO database (http:// www.ncbi.nlm.gov/geo/accession number GSE425/8653, Supplementary Figure S1a and b). 14,15 By gene-expression data mining, a significant downregulation of ICSBP in AML with t(15;17) and with t(8;21), and a tendency of ICSBP downregulation in -7/del(7q) was found (Supplementary Figure S1c). Furthermore, an ICSBP downregulation was published for therapy-induced AML with -5/del(5q).…”
Section: Conflict Of Interestmentioning
confidence: 99%